A study on the relationship between mindfulness and work performance of web editors: Based on the chain mediating effect of workplace spirituality and digital competencies - He, Jiazi; Li, Xinwei; Wang, Huiyi; Xu, Zhiwu (Frontiers in Psychology, 2023)
Introduction Based on the job demands-resources model, this study aims to explore the relationship between mindfulness in web editors, work performance, workplace spirituality, and digital competencies. Methods Online data from the Tencent Questionnaire Platform was used to examine the proposed research model. We distributed questionnaires to new media companies, and a total of 431 valid questionnaires were collected. Results and Discussion The results suggested that mindfulness in web editors can improve workplace spirituality, digital competencies, and work performance. In addition, workplace spirituality was found to act as a mediator between mindfulness and work performance. And, digital competencies did not play a mediating role between mindfulness and work performance, but workplace spirituality and digital competencies played a chain mediating role between mindfulness and work performance. The study explained the internal impact mechanism of mindfulness on work performance in web editors, and proposed methods to improve mindfulness, revealing the chain mediating role of workplace spirituality and digital competencies in the impact of mindfulness on work performance, which might provide new insights into existing research. It can provide a reference for new media companies to manage the team of web editors and improve the work performance of web editors.